Tingimento de tecido de lã com corante natural extraído do fruto da Cinnamomum verum J. Presl. - Ferreira , Fabricio Leal (2019)
On market requirements and increased awareness of producers and consumers in relation to the problems caused by the use of synthetic dyes, using natural dyes can be considered a cost-effective alternative and sustainable textile dyeing, since they present a low risk to the environment, human health and good biodegradability. The Cinnamomum verum J. Presl is a plant in the evergreen trees, whose fruits contain anthocyanin derivatives that can be used as dyes for dyeing of fabrics. The study presented here evaluated the process of dyeing wool with natural dye extracted from the fruit of the Cinnamomum verum J. Presl in order to find the optimum conditions of dyeing, such as temperature, pH and time. Dyed samples were evaluated against the intensity of color and influence of potassium alum in mordant washing of dyed fabrics through colorimetric analysis performed in spectrophotometer through the CIELab system. It was found that the conditions presented greater intensity of color of fabric at pH 4, 100° C with dyeing time of 60 minutes. The results were used to investigate the kinetics of dyeing and dyeing process balance through the adsorption isotherms. The study showed that the kinetic equation of pseudo-second order is the one that best represents the kinetic mechanism of the dyeing of wool and is associated with the chemical adsorption process. The adsorption isotherm Langmuir-Freundlich best set the experimental data, showing significant contribution of the chemical adsorption process in a monolayer. The results obtained indicate that the coloring of the fruit extract of Cinnamomum verum j. Presl shows itself as a promising source to be used as a natural dye in dyeing of wool fabrics.